PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, KUALITAS AUDIT DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN KARAKTER EKSEKUTIF SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lia Ira Sahara (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the ability of independent commissioners, audit committees, audit quality and capital intensity to influence tax avoidance with the executive character as a moderating variable. This type of research uses a quantitative approach, which means that it is a research method based on the philosophy of positivism, is used to research a specific population or sample, collect data, use research instruments, analyze quantitative or statistical data, with the aim of testing hypotheses that have been determined by taking the company LQ 45 as a sample. The analysis technique used in this research is multiple linear regression with a significance level of 5%. Statistical testing using IBM Statistic SPSS V.25. The results of this study indicate that independent commissioners, audit committee, audit quality and capital intensity have a simultaneous and partial effect on tax avoidance, executive character does not moderate the effect of independent commissioners on tax avoidance, executive character moderates the effect of audit committee on tax avoidance, executive character does not moderate the effect of audit quality on tax avoidance, executive character moderates the effect of capital intensity on tax avoidance.